2013
DOI: 10.4329/wjr.v5.i7.259
|View full text |Cite
|
Sign up to set email alerts
|

Prostate magnetic resonance imaging at 3 Tesla: Is administration of hyoscine-N-butyl-bromide mandatory?

Abstract: AIM:To evaluate the value of administration of hyoscine-N-butyl-bromide (HBB) for image quality magnetic resonance imaging (MRI) of the prostate. METHODS:Seventy patients were retrospectively included in the study. Thirty-five patients were examined with administration of 40 milligrams of HBB (Buscopan ® ; Boehringer, Ingelheim, Germany); 35 patients were examined without HBB. A multiparametric MRI protocol was performed on a 3.0 Tesla scanner without using an endorectal coil. The following criteria were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Our study results showed no benefit with HBB, neither when used exclusively, nor in combination with ME and or DR. We observed a positive trend toward better delineation of anatomic detail and less motion artifacts on T2w sequences for R1 only; however, the difference was not statistically significant. These results are in line with Wagner [9] and Roethke et al [12]. Still, the data must be interpreted with caution due to comparably lower field strength (1.5T) used by Wagner et al [9] in their study setting.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our study results showed no benefit with HBB, neither when used exclusively, nor in combination with ME and or DR. We observed a positive trend toward better delineation of anatomic detail and less motion artifacts on T2w sequences for R1 only; however, the difference was not statistically significant. These results are in line with Wagner [9] and Roethke et al [12]. Still, the data must be interpreted with caution due to comparably lower field strength (1.5T) used by Wagner et al [9] in their study setting.…”
Section: Discussionsupporting
confidence: 84%
“…In this context, antispasmodic agents such as hyoscine N-butylbromide (HBB) are widely used for suppression of bowel peristalsis. However, study results regarding the use of HBB are equivocal, as some authors did find positive effects on artifact reduction and/or IQ [7,11], while others did not [9,12].…”
Section: Introductionmentioning
confidence: 93%
“…Butylscopolamine for prostate imaging has been reported, but some reports indicate that butylscopolamine is unnecessary [7][8][9][10]. The reason for these results is that organs including the prostate, bladder, rectum, and lymph nodes are not different whether or not butylscopolamine is used.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an intestinal spasmolytic leads to a relevant reduction of artifacts caused by the natural movement of the bowel and thus to an increase in image quality and should therefore be applied routinely [20][21][22][23]. Individual studies, but without a prospective comparison within a patient and in some cases with the use of an endorectal coil, assessed the effect to be lower [24,25].…”
Section: Antispasmoticsmentioning
confidence: 99%